The energy of Russia : hydrocarbon culture and climate change - Tynkkynen, Veli-Pekka (Edward Elgar, 2020)
This timely book analyses the status of hydrocarbon energy in Russia as both a saleable commodity and as a source of societal and political power. Through empirical studies in domestic and foreign policy contexts, Veli-Pekka Tynkkynen explores the development of a hydrocarbon culture in Russia and the impact this has on its politics, identity and approach to climate change and renewable energy. Cogent and compelling, this book demonstrates how the Russian state leverages its oil and gas reserves in order to create and maintain power both domestically and internationally. Tynkkynen uses empirical studies of key topics such as the national gas programme Gazprom, the Arctic, climate discourse and anthropogenic climate change denial, and the Russia-Finland energy trade to critically examine the situation. The book concludes with a convincing argument for the potential of renewable energy to build a more resilient and sustainable future for Russia and how this might be achieved. This will prove crucial reading for scholars and students of Russian and Eastern European studies and energy and environmental studies, as well as geographers, anthropologists and political scientists. Those working in governments, international organizations and corporations with an interest in Russian energy will also find its insights useful.